Comparative Study of Lifestyle in Postmenopausal Women with Normal and Abnormal Bone Marrow Densitometries - Z Alizadeh; F Koohdani; B Larijani; N Hatmi; Sh Khosravi; G Sotoudeh (Tehran University of Medical Sciences, 2010)
Background & Objective: Osteoporosis is a serious public health concern known to have several etiologic factors. This study compared lifestyles among postmenopausal women with normal and abnormal bone marrow densitometries (BMD). Methods & Materials: In this case-control study, 81 postmenopausal women (33 cases with abnormal BMD and 48 control individuals with normal BMD) were selected using simple random sampling from Osteodensitometry center of Shariati hospital in Tehran. The BMD at lumbar spine and femoral neck had been measured with DXA. The Lifestyle was assessed using a questionnaire containing items about taking calcium, vitamin D, hormones, and Alendronat, doing physical activity, consuming tea and cola, and smoking. Reproductive characteristics were also collected via a questionnaire. Data were analyzed using χ2 test and independent sample t-test. Crude and adjusted odds ratios and relevant 95% confidence intervals were calculated through logistic regression, using SPSS v.13. Results: The results showed significant differences between two groups in weight (P>0.001), BMI (P=0.022), number of pregnancies (P=0.002), number of children (P=0.004), duration of lactation (P=0.0002), dietary calcium intake (P≤0.001), and period of calcium supplement intake (P=0.002). The average of acquired scores of lifestyle factors in the case group was significantly lower than the control group (P=0.037). Inappropriate lifestyle had increased risk of the disease (OR=3.36, 95%, CI: 1.10-10.26). Meanwhile in the multivariate analysis, only insufficient intake of calcium was found to be a risk factor (P=0.002) for osteoporosis. Conclusion: In conclusion, the results of this study showed positive effect of calcium intake on bone mineral density.